2020
DOI: 10.1002/ece3.6318
|View full text |Cite
|
Sign up to set email alerts
|

Complex interactions between bacteria and haemosporidia in coinfected hosts: An experiment

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
(54 reference statements)
1
12
1
Order By: Relevance
“…Another lineage detected in House Finches here (RWB01) has been reported previously infecting a Song Sparrow (Melospiza melodia; Szymanski and Lovette, 2005); while a Plasmodium haplotype reported in House Finches by Kimura et al (2006) corresponds to a generalist lineage found in 27 different host species (Fallon et al 2005). It is notable that the three Plasmodium lineages (PADOM11, SEIAUR01, and WW3) infecting House Finches in more recent studies (Dhondt et al 2017;Reinoso-Pe ´rez et al 2020) were still detected in the current survey, with PADOM11 being the most common lineage infecting House Finches. Nevertheless, in our current 2-yr survey no lineage of Leucocytozoon infecting House Finches was detected, contrasting with what Reinoso-Pe ´rez et al (2020) reported the previous year.…”
Section: Discussionsupporting
confidence: 71%
“…Another lineage detected in House Finches here (RWB01) has been reported previously infecting a Song Sparrow (Melospiza melodia; Szymanski and Lovette, 2005); while a Plasmodium haplotype reported in House Finches by Kimura et al (2006) corresponds to a generalist lineage found in 27 different host species (Fallon et al 2005). It is notable that the three Plasmodium lineages (PADOM11, SEIAUR01, and WW3) infecting House Finches in more recent studies (Dhondt et al 2017;Reinoso-Pe ´rez et al 2020) were still detected in the current survey, with PADOM11 being the most common lineage infecting House Finches. Nevertheless, in our current 2-yr survey no lineage of Leucocytozoon infecting House Finches was detected, contrasting with what Reinoso-Pe ´rez et al (2020) reported the previous year.…”
Section: Discussionsupporting
confidence: 71%
“…For example, increased reproductive success (increased clutch size and fledglings) was found among individuals with coinfections ( Marzal et al, 2008 ; Pigeault et al, 2018 ), while other host species exhibited reductions in fitness (e.g., survivability; Pigeault et al, 2018 ). Further, interspecific competition between Leucocytozoon and Plasmodium may occur in hosts eliciting hosts to exhibit trade-off responses when other novel infections are present ( Reinoso-Pérez et al, 2020 ). As coinfections may have important consequences on host fitness, the detection of multiple lineages of Leucocytozoon in both blood and muscle samples warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, multiple strains or even different species of these malaria parasites infect hosts in wild populations (Palinauskas et al 2016, Pigeault et al 2020, Reinoso-Pérez et al 2020, Valkiūnas et al 2003. Furthermore, co-infecting parasites interact not only with the 4 host but with each other (Bose et al 2016).…”
Section: )mentioning
confidence: 99%